THE USE OF STORY BOOK â€œPEEWEE AT THE FARMâ€ IN INTRODUCING ENGLISH TO KINDERGARTEN - Rita, .; ., Regina; Sada., Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract. This research was conducted in Level B kindergarten students at TK Kristen Immanuel I Pontianak which is located at JL. Gajah Mada No. 250, Pontianak, Kalimantan Barattoprove that the use of story book â€œPee Wee at the Farmâ€ is an effective way to introduce English.In collecting the data, the researcher used qualitative and quantitative assessment by using interview and observation sheet as the qualitative assessment, and oral test as the quantitative assessment where the students were asked some questions and repeated them.In the result it can be found that introducing English to kindergarten students using story book â€œPee Wee at the Farmâ€ was an effective way to attract and motivate the studentsâ€™ interest in English.It was shown that all of the 20 students got the extraordinary score, means that the students were able to repeat and understand more than 7 simple sentences taught based on the story book. There were 18 students got the perfect score, means that the students were able to repeat and understand all 10 simple English sentences. There was only one student that was able to repeat and understand 7 sentences and only one student that was able for 8 sentences. Keywords: English Story Book, Introduce, Effectiveness. Â Abstrak. Penelitian ini dilaksanakan pada siswa taman kanak-kanak Tingkat B TK Immanuel I yang terletak di Jl. Gajah Mada No. 250, Pontianak Kalimantan Barat untuk membuktikan bahwa penggunaan buku â€œPee Wee at the Farmâ€ adalah sebuah cara yang efektif untuk memperkenalkan bahasa Inggris. Dalam mengumpulkan data, peneliti menggunakan penilaian kualitatif dan kuantitatif dengan menggunakan lembat wawancara dan observasi sebagai penilaian kualitatif, dan uji oral sebagai penilaian kuantitatif dimana siswa ditanyakan dan diminta mengulangi materi. Hasil yang ditemukan adalah bahwa memperkenalkan bahasa Inggris kepada siswa taman kanak-kanak menggunakan buku cerita â€œPee Wee at the Farmâ€ adalah sebuah cara yang efektif untuk menarik dan memotivasi ketertarikan siswa pada bahasa Inggris. Ditunjukkan bahwa ke-20 siswa memperoleh nilai diatas rata-rata, dimana mereka mampu mengulang dan memahami lebih dari 7 sampel kalimat sederhana yang diajarkan dari buku cerita tersebut. Ada 18 siswa memperoleh nilai sempurna, yaitu mereka yang mampu mengulangi dan memahami 10 kalimat Inggris sederhana. Hanya ada 1 siswa yang mampu mengulangi dan memahami 7 kalimat. Â Kata kunci : Buku Bahasa Inggris, Mengenalkan, Efektifitas